2015
DOI: 10.18203/2394-6040.ijcmph20151033
|View full text |Cite
|
Sign up to set email alerts
|

A study to know infant and young child feeding practices of mothers attending mother and child health clinic at a tertiary care teaching hospital, Davangere, India

Abstract: Background: Feeding pattern during infancy has several health related implications. Infant and young child feeding [IYCF] practices comprising breastfeeding as well as complimentary feeding have major role in determining the nutritional status of children. Most of the studies conducted in India focus on breastfeeding aspects only, our study will also include practices regarding complementary diet diversity & frequency aspects of IYCF using the WHO standard IYCF indicators. Objective of the study was to know t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Poor feeding and repeated infections resulted in 30% of stunted under-five children world-wide. 3 Malnutrition alone is responsible for 67% of child death in India. 4 In all settings that includes irrespective of place of delivery, rich and poor, urban and rural area breastfeeding had positive effects on the health of infants and mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Poor feeding and repeated infections resulted in 30% of stunted under-five children world-wide. 3 Malnutrition alone is responsible for 67% of child death in India. 4 In all settings that includes irrespective of place of delivery, rich and poor, urban and rural area breastfeeding had positive effects on the health of infants and mothers.…”
Section: Introductionmentioning
confidence: 99%
“…It is considerably higher than that found in the studies of Davalgi et al where it was 48% and Karol et al where it was 36.6%. 26,27 These differences may be because these studies were conducted in healthcare facilities and not community based like the current study. The result was also higher than the studies of Khan et al where it was 38.2%.…”
Section: Discussionmentioning
confidence: 87%
“…15 Minimum meal frequency in the present study was observed to be 81.3%, whereas studies by Khan et al and Davalgi et al reported lower rates of 48.6% and 48.0% respectively. 11,16 In contrast, a study done in Gujarat observed that 95.6% of breast-fed children were fed at least the minimum number of times recommended. 17 Minimum acceptable diet is a summation indicator of both minimum dietary diversity and minimum meal frequency and indirectly reflects the true picture of IYCF practices.…”
Section: Discussionmentioning
confidence: 95%